Faktor-Faktor yang Berhubungan dengan Kecemasan Ibu Hamil Terpapar Covid-19 di Wilayah Kerja Puskesmas Tanjung Iman Kecamatan Kaur Tengah Kabupaten Kaur Provinsi Bengkulu - Lisa Depitasari; Aprina Aprina; Rilyani Rilyani (Malahayati Nursing Journal, 2023)
ABSTRACT Anxiety is excessive worry about things that will happen. Anxiety can attack anyone, including pregnant women. Covid-19 was first detected in Indonesia on March 2, 2020, As of August 23, 2020, Indonesia has reported 153.535 positive cases, with 6.680 deaths, 107.500 recoveries, and 39.355 active cases. The Indonesian government tested 1.157.18 people out of a total of 269 million people, or around 292 people per million population. of this study was to determine the factors related to the anxiety of pregnant women exposed to Covid-19 in the Tanjung Iman Health Center Work Area, Kaur Tengah District, Bengkulu Province Kaur.This research is a quantitative research, with an analytical research design with a Cross Sectional approach. The population in this study with all pregnant women TM I - III as many as 381 pregnant women with a sample of 130 pregnant women. This research was conducted at the Tanjung Iman Health Center, Kaur Tengah District, Kaur Regency, Bengkulu Province, on April 25-May 23, 2022. The data was collected using a questionnaire. Data analysis was univariate and bivariate (chi square) it is known that respondents with maternal higher education are 78 (60.0%), respondents with good maternal knowledge are 66 (50.8%), respondents with positive families are 75 (57.7%), respondents with a history of pregnancy examination according to as many as 70 (53.8%), respondents with anxiety pregnant women are not anxious as many as 90 (69.2%). There is a relationship between education (p-value = 0.033), knowledge (p-value = 0.001), family support (p-value = 0.001), history of prenatal care (p-value = 0.021) with the anxiety of pregnant women exposed to covid-19 at the Tanjung Iman Health Center, Kaur Tengah District, Kaur Regency, Bengkulu Province. Suggestion: always provide education to patients about implementing health protocols to prevent the transmission of the covid-19 virus. Keywords: Education, Knowledge, Family Support, History of Pregnancy Examination, Maternal Anxiety.  ABSTRAK Kecemasan adalah kekhawatiran yang berlebihan tentang hal-hal yang akan terjadi. Kecemasan bisa menyerang siapa saja, termasuk  ibu hamil. Covid-19 pertama kali dideteksi di indonesia pada 2 Maret 2020, Hingga 23 Agustus 2020, Indonesia telah melaporkan 153.535 kasus positif, dengan 6.680 kematian, 107.500 pemulihan, dan 39.355 kasus aktif. Pemerintah Indonesia menguji 1.157.18 orang dari total 269 juta penduduk, atau sekitar 292 orang per juta penduduk. Penelitian ini untuk mengetahui Faktor-Faktor Yang  Berhubungan Dengan Kecemasan Ibu Hamil Terpapar Covid-19 Di Wilayah Kerja Puskesmas Tanjung Iman Kecamatan Kaur Tengah Kabupaten Kaur Provinsi Bengkulu. Penelitian ini merupakan penelitian kuantitatif, dengan rancangan penelitian analitik dengan pendekatan Cross Sectional. Populasi dalam penelitian ini dengan seluruh ibu hamil TM I - III sebanyak  381 ibu hamil dengan sampel sebanyak 130 ibu hamil. Penelitian ini telah dilakukan di Wilayah Kerja Puskesmas Tanjung Iman Kecamatan Kaur Tengah Kabupaten Kaur Provensi Bengkulu pada tanggal 25 April-23 Mei 2022. Pengumpulandata menggunakan kuesioner. Analisis data secara univariat dan bivariat (chi square). Diketahui responden dengan pendidikan tinggi ibu sebanyak 78 (60,0%), responden dengan pengetahuan ibu baik sebanyak 66 (50,8%), responden dengan keluarga positif sebanyak 75 (57,7%), responden dengan riwayat pemeriksaan kehamilan sesuai sebanyak 70 (53,8%), responden dengan kecemasan ibu hamil tidak cemas sebanyak 90 (69,2%). Ada hubungan pendidikan (p-value = 0,033), pengetahuan (p-value = 0,001), dukungan keluarga (p-value = 0,001), riwayat pemeriksaan kehamilan(p-value = 0,021) dengan Kecemasan Ibu Hamil Terpapar Covid-19 di Puskesmas Tanjung Iman Kecamatan Kaur Tengah Kabupaten Kaur Provinsi Bengkulu. Saran : dapat memberikan edukasi kepada pasien tentang melaksanakan protokol kesehatan untuk mencegah penularan virus covid-19. Kata Kunci: Pendidikan, Pengetahuan, Dukungan Keluarga, Riwayat Pemeriksaan Kehamilan, Kecemasan Ibu